Pathophysiology of human hearing loss associated with variants in myosins - Miyoshi, Takushi; Belyantseva, Inna A.; Sajeevadathan, Mrudhula; Friedman, Thomas B. (Frontiers in Physiology, 2024)
Deleterious variants of more than one hundred genes are associated with hearing loss including MYO3A, MYO6, MYO7A and MYO15A and two conventional myosins MYH9 and MYH14. Variants of MYO7A also manifest as Usher syndrome associated with dysfunction of the retina and vestibule as well as hearing loss. While the functions of MYH9 and MYH14 in the inner ear are debated, MYO3A, MYO6, MYO7A and MYO15A are expressed in inner ear hair cells along with class-I myosin MYO1C and are essential for developing and maintaining functional stereocilia on the apical surface of hair cells. Stereocilia are large, cylindrical, actin-rich protrusions functioning as biological mechanosensors to detect sound, acceleration and posture. The rigidity of stereocilia is sustained by highly crosslinked unidirectionally-oriented F-actin, which also provides a scaffold for various proteins including unconventional myosins and their cargo. Typical myosin molecules consist of an ATPase head motor domain to transmit forces to F-actin, a neck containing IQ-motifs that bind regulatory light chains and a tail region with motifs recognizing partners. Instead of long coiled-coil domains characterizing conventional myosins, the tails of unconventional myosins have various motifs to anchor or transport proteins and phospholipids along the F-actin core of a stereocilium. For these myosins, decades of studies have elucidated their biochemical properties, interacting partners in hair cells and variants associated with hearing loss. However, less is known about how myosins traffic in a stereocilium using their motor function, and how each variant correlates with a clinical condition including the severity and onset of hearing loss, mode of inheritance and presence of symptoms other than hearing loss. Here, we cover the domain structures and functions of myosins associated with hearing loss together with advances, open questions about trafficking of myosins in stereocilia and correlations between hundreds of variants in myosins annotated in ClinVar and the corresponding deafness phenotypes.